Acoustically excited interaction of gas bubbles in a liquid with centers located on a plane - A.I. Davletshin (Учёные записки Казанского университета: Серия Физико-математические науки)
The hydrodynamic interaction of weakly non-spherical gas bubbles in a liquid was made in the case of the bubbles located in the antinode of an intense ultrasonic standing wave, where the pressure varies harmonically. The influence of the interaction on the radial pulsations of the bubbles, their spatial displacements, and the deformations of their surfaces were investigated. Various mutual arrangements of bubbles, in which one of the bubbles is in their center and the others are evenly distributed on a series of concentric circles in a plane, were under consideration.